Análisis de las fases lunares en relación al prendimiento de ramillas de cacao CCN-51 - Barragán Aldaz, Byron Fabricio (2020)
The purpose of this study is to be able to collaborate from the technical-agricultural point of view with the cocoa community in general; It is necessary to indicate that the cultivation of cocoa is of high commercial value for Ecuador, and that is why through this bibliographic study it is intended to give an alternative on the management of cocoa cultivation in terms of the influence of the lunar phases, since there are several experimental studies that maintain that there is a wide relationship between the plant and the moon, which makes it worth noting that after a thorough analysis of various investigations, such as; Undergraduate and postgraduate thesis, high-impact papers, bibliographic reviews, etc., it was noted that the best time or moon phase for the work of cutting the crooks and later their sowing, as well as various tasks are the phases of the waxing and waning moon , because the gravitational attraction on the xylem, phloem (liquid or semi-liquid substances) make their levels low in plants favoring a timely and effective take-off, not so with the other lunar phases of this study, which are those of the moon. full and new moon. Therefore, this is a possible solution that will help the management of the cocoa twigs for their selection and planting.